Estimation of respiratory syncytial virus-associated hospital admissions in five European countries: a modelling studyResearch in context - Caroline Klint Johannesen; David Gideonse; Richard Osei-Yeboah; Toni Lehtonen; Ombeline Jollivet; Rachel A. Cohen; Arantxa Urchueguía-Fornes; María Herrero-Silvestre; Mónica López-Lacort; Rolf Kramer; Thea K. Fischer; Terho Heikkinen; et al. (The Lancet Regional Health. Europe)
Summary: Background: Respiratory syncytial virus (RSV) can cause severe disease, notably among infants, older adults, and individuals with comorbidities. Non-systematic testing and differences in coding practices affect direct measures of the hospital disease burden. We aim to tackle this issue and estimate RSV-associated respiratory hospital admissions through time series modelling of hospital admissions. Methods: The number of RSV hospital admissions in Denmark, England, Finland, the Netherlands, and Spain were estimated with attribution analyses, using age-specific respiratory tract infection (RTI) admissions combined with virological data, both from routinely collected healthcare data. Analyses covered the years 2016–2023. Findings: The attributed incidence of RSV per 100,000 children 0–2 months ranged from 1715 in Denmark to 3842 in England. In older adults, substantial differences in the incidence of ICD-10 coded RSV hospitalisations were found, while the attributed RSV incidence was more comparable, ranging from approximately 100 per 100,000 in adults 65–74 years to 200 per 100,000 persons 75–84 years and 500 per 100,000 persons 85 years and older. Interpretation: RSV-attributed time series exhibit a high degree of synchronicity between participating countries, suggesting that this method for attribution addresses the known issues with underdiagnosis and misclassification. In the older age groups, a substantial proportion of RTI hospitalisations is attributed to RSV, underscoring the relevance of RSV as a cause of severe respiratory infections. Funding: This project has received funding from the Innovative Medicines Initiative 2 Joint Undertaking under grant agreement 101034339. This Joint Undertaking receives support from the European Union’s Horizon 2020 research and innovation programme and EFPIA.